Как собака друга искала: сказки / худ. О. Крупенкова - Крупенкова О. (Колобок, 2006)
Экземпляры: ФО - 27; 28; (20110303) / Инвентарный номер: 42419 / Цена: 45.10 / Сис.шифр: Сб мл. 42419 / Авт.знак: К 16 / ББК: Сб мл.